ASPEK BAURAN PEMASARAN YANG MEMPENGARUHI KEPUTUSAN UNTUK MEMILIH STUDI DI MM UGM-KAMPUS DOMISILI JAKARTA - , Adrian Rengga Mukti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze to analyze the influence factors of marketing mix (product, price, promotion, place, people, process, and physical evidence) against the decision to choose studies at MM UGM - campus residence in Jakarta. The method of analysis used to support the proposed hypothesis is multiple linear regression analysis method. The sample used in this research that the freshmen and sophomores MM UGM Jakarta. Samples were taken using purposive sampling method, the number of respondents is 100. Results of this study showed that, of the marketing mix has significant on to influence the decision factors for selecting studies MM UGM - campus residence Jakarta but several factors such as location, promotion, people, and processes have little effect, as well as the value of R Square indicates that factors mix has little effect on the decision to choose studies at MM UGM - campus residence in Jakarta. Factors - physical evidence (physical evidence) to be the most influential among other 7P against the decision of choosing studies in MM Jakarta campus residence.